Pathophysiology of severe traumatic brain injury and management of intracranial hypertension - Juškys, Raimondas; Hendrixson, Vaiva (Lietuvos chirurgija, 2019)
It is well recognized that severe traumatic brain injury causes major health and socioeconomic burdens for patients their families and society itself. Over the past decade, understanding of secondary brain injury processes has increased tremendously, permitting implementation of new neurocritical methods of care that substantially contribute to improved outcomes of such patients. The main objective of current treatment protocols is to optimize different physiological measurements that prevent secondary insults and reinforce the ability of the brain to heal. The aim of this literature review is to uncover the pathophysiological mechanisms of severe traumatic brain injury and their interrelationship, including cerebral metabolic crisis, disturbances of blood flow to the brain and development of edema, putting emphasis on intracranial hypertension and its current management options.
Keywords: traumatic brain injury; head injury; head trauma; critical care; intracranial hypertension